Applying the Theory of Planned Behaviour to predicting online safety behaviour - Burns, Sarah; Roberts, Lynne (Macmillan Publishers Ltd., 2013)
A widely promoted preventative measure against becoming a victim of cybercrime is the control of personal information online; however, little is known about what predicts the use of this type of protective safety behaviour. This study examines the utility of the Theory of Planned Behaviour in predicting online protective behaviours. Participants (N=150) completed measures of online privacy attitudes, normative influence, perceived behavioural control (PBC), intention to use and actual use of online protective behaviours. Path analysis indicated the effects of online privacy attitudes and normative beliefs on online protective safety behaviours were mediated through intention, while PBC had a significant direct effect on online protective safety behaviours. The model explained 81 per cent of the variance in protective online safety behaviours. The results of this study facilitate understanding of the psychological processes underlying the use of online protective behaviours, and can be used in the development of educational materials and cyber-identity theft prevention strategies.